Use of Internet Vs Book as a Source of Information among Nursing Undergraduates, AIIMS, New Delhi (International Journal of Nursing Education, 2019)
Background: The Internet has become part and parcel of every walk of life across the world. Nursing students are in touch with books and the internet in order to acquire information for their academic learning. Aim: This study explored use of the internet Vs book as a source of information among nursing undergraduates and how these sources are influencing their academic performances. Method: A descriptive Survey Design was adopted; 197 students of B.Sc. (Honors) Nursing students recruited to study by convenience sampling. Data was collected by using demographic profile, likert scale on web based learning, likert scale on traditional book based learning and record analysis for academic performance. Results: Students showed a greater appreciation for books than for Internet (Average Books Score was greater than Average Internet Score). However, the difference was not significant at the 5% level, though it was significant at the 10% level. Increased use of Internet for Academic Activity was not associated with better academic performance as measured by the percentage of marks obtained by the student. Conclusion: The effects of Internet use on academic performance and the higher rating of books as compared to the Internet is a clear indication that while internet is useful for study it cannot be a universal and complete solution.